Bone Status in Obese, Non-diabetic, Antipsychotic-Treated Patients, and Effects of the Glucagon-Like Peptide-1 Receptor Agonist Exenatide on Bone Turnover Markers and Bone Mineral Density - Eriksson, Robert; Broberg, Brian V.; Ishøy, Pelle L.; Bak, Nikolaj; Andersen, Ulrik B.; Jørgensen, Niklas R.; Knop, Filip K.; Ebdrup, Bjørn H. (Frontiers in Psychiatry, 2019)
Background: Low bone mineral density (BMD) may constitute an underestimated comorbidity in schizophrenia patients undergoing long-term antipsychotic treatment. Glucagon-like peptide 1 (GLP-1) receptor agonists are antidiabetic drugs, which may also affect bone turnover. Methods: In planned secondary analyses of a 3 months, double-blind, randomized, placebo-controlled trial (n = 45), we explored effects of the GLP-1 receptor agonist exenatide 2 mg once-weekly (n = 23), or placebo (n = 22) on bone turnover markers (BTMs) and BMD in chronic, obese, antipsychotic-treated patients with schizophrenia spectrum disorder. Baseline BTMs were compared to sex- and age-adjusted reference values from a Danish population cohort, and T- and Z-scores were calculated for BMD. Results: In women (n = 24), all baseline BTM measurements of procollagen type I N-terminal propeptide (PINP) and C-terminal cross-linking telopeptide of type I collagen (CTX) were within reference values. In men (n = 21), 5% displayed lower PINP and 14% displayed lower CTX. One patient displayed BMD Z-score < −2, and 23% of patients (17% of women and 29% of men) displayed −2.5 < T-scores < –1 indicating osteopenia, but none had osteoporosis. After treatment, PINP decreased at trend level significance (P = 0.05), and body mass index BMD increased for L2–L4 (P = 0.016). No changes in bone markers were significant after correction for mean prolactin levels. Conclusions: Sex- and age-adjusted measures of bone status in chronic, obese, antipsychotic-treated patients appeared comparable to the reference population. Subtle changes in bone markers during 3 months exenatide treatment may suggest beneficial effects of GLP-1 receptor agonists on bone status in antipsychotic-treated patients, and further studies should consider the potential influence of prolactin.